FIToplankton: Wireless Controlled Remotely-operated Underwater Vehicle (ROV) for Shallow Water Exploratio - Muhammad Ikhsan Sani; Simon Siregar; Aris Pujud Kurniawan; M. Abid Irwan (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Remotely Operated Vehicle (ROV) for underwater exploration is typically controlled using umbilical cable connected to ground control station. Unfortunately, while it’s used for power distribution and data transmission, it also obstruct the movement of ROV especially for shallow water (<50 cm). This paper proposed an alternative method for controlling ROV using wireless remote control system. This work also aims to explore the possibility of using RF wireless technology between 420-450 MHz as underwater communication system. Furthermore, the control system was used to manage actuators i.e. DC motor and bilge pump for maneuvring and picking small size cargo. To help the ROV to hold on a desired, Inertial Measurement Unit (IMU) is installed on board ROV within maximum deviation 0.2 m/s2. The prototype of the system has been successfully implemented and evaluated to confirm the  functionality and the feasibility of the proposed approach.